Determinação do dano em pavimentos asfálticos por meio da combinação do modelo S-VECD com análises elásticas - Santiago, Lucimar da Silva (2022)
Performance prediction of materials in the field is one of the challenges in pavement engineering. Such prediction requires mathematcal modeling that relates materials characterizaon in the laboratory and the performance of these same materials in actual structures. Since fatigue damage is one of the main distresses in Brazilian asphaltic pavements, the objective of this work is to present a methodology to determine such distress using linear elastic analysis, having as inputs fatigue damage evolution parameters obtained in laboratorial tests. Given the importance of temperature and vehicle speed in roadways for pavement performance with respect to fatigue damage, these two parameters are also considered in the simplified analysis. At the end, it is presented a practical example with the main steps of the developed methodology, which is programmed in a specific pavement design software. The proposed methodology is a step in enhancing field-laboratory correlation, facilitating the behavior prediction of asphaltic materials in real pavements.